Menstrual cycle changes in vagally-mediated heart rate variability are associated with progesterone: evidence from two within-person studies - Schmalenberger, Katja; Eisenlohr-Moul, Tory A.; Jarczok, Marc N.; Eckstein, Monika; Schneider, Ekaterina; Brenner, Ines; Duffy, Kathleen; Schweizer-Schubert, Sophie; Kiesner, Jeff; Thayer, Julian F.; Ditzen, Beate (Journal of Clinical Medicine, 2020)
A recent meta-analysis revealed that cardiac vagal activity (mostly indicated by vagally-mediated heart rate variability; HRV) decreases significantly from the follicular to luteal menstrual cycle phase in naturally-cycling participants. However, the question remains as to whether cyclical changes in estradiol (E2), progesterone (P4), or both are responsible for HRV fluctuations. We present the first studies to use repeated measures of E2, P4, and HRV across the cycle to model both the unique and interactive effects of person-centered E2 and P4 on HRV in multilevel models. In study one, 40 naturally-cycling participants were assessed weekly across four weeks, and were blind to the cycle focus of the study. In study two, 50 naturally-cycling participants were examined in three precisely defined cycle phases via ovulation testing. Both studies revealed that only P4 was correlated with HRV, such that higher-than-usual P4 significantly predicted lower-than-usual HRV within a given participant. In line with this, cycle phase comparisons revealed lower HRV in the mid-luteal phase (characterized by elevated P4) than in other phases. No significant main or interactive effects of E2 on HRV were found. Future female health studies should investigate individual differences in these effects and potential consequences of cyclical HRV changes on daily functioning.
Gesehen am 15.05.2020